The effectiveness of the project management life cycle in Eskom Limpopo Operating Unit - Baloyi, Gidion (University of Limpopo, 2015)
South Africa is a developing state; the roles of the state owned entities in encouraging economic growth and contributing to the mitigation of unemployment and poverty eradication are unavoidable. Project management from an engineering development perspective and as an industrial discipline has been investigated and published throughout the past period. It could be said that the subject is mature, as recent publications on project management fail to bring new knowledge to light particularly in Eskom. This mini dissertation studies the most significant serious success factors in the effective project management in different departmental conditions within Eskom. Projects are being used daily in Eskom to achieve the company goal. In recent years researchers have become increasingly interested in factors that may have an impact on project management effectiveness and the success of projects. However, there is little research that shows how effectively projects are managed in a business organisational context like Eskom. My Study aims to partly fill this gap by presenting results from a case study and surveys of Eskom as an organisation practising project management. It also aims to investigate the effectiveness of project management in terms of Eskom Divisional structures, technical competency, Eskom Project leadership ability and the characteristics of an effective project manager. In managing projects, it is significant to know how to handle both the tools and the people and to achieve a balance between the two. Experience, especially in the management of change was perceived to be a significant factor in project success
Thesis (MBA.) -- University of Limpopo, 2018
Keywords: Project management; Eskom; Limpopo Operating Unit; Project management; Participatory monitoring and evaluation (Project management)